BUNGA RAMPAI DESAIN : PAMERAN SENI DAN DESAIN SEBAGAI WUJUD KOLABORASI KREATIF DALAM PENGABDIAN MASYARAKAT - Santi Widiastuti; Irdha Yunianto; Budi Hartono; Widya Ariyani; Julitta Dewayani; Zahra Dinul Haq; Sulartopo Sulartopo; Khoirur Rozikin; Iman Saufik Suasana (CV. Denasya Smart Publisher, 2025)
The community service program entitled Bunga Rampai Desain represents the contribution of the Visual Communication Design Study Program at STEKOM University in promoting public literacy on art and design as educational, social, and cultural mediums. Held at Tan Art Space Gallery in Semarang, the program integrated an exhibition of visual works such as posters, installations, photography, and graphic design with interactive workshops and open discussions. The implementation involved students, academics, artists, and local communities to create a participatory and collaborative ecosystem. Evaluation results indicate a significant increase in public appreciation of visual arts, as well as the emergence of interdisciplinary engagement. Students gained direct experience in curating, event management, and public visual communication. These findings affirm that visual-based approaches can serve as effective strategies in community engagement programs, particularly in fostering critical awareness and sustaining creative dialogue. The program provides a model for future replication and development of similar initiatives